2013
DOI: 10.9790/2380-0334851
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Oral and Intraocular Routes of Administration of Newcastle Disease Vaccine, La Sota in Adult Chickens.

Abstract: Two hundred and fifty (250)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…This might account for the preferential protection offered by the oral route compared to the ocular one. This report is however at variance with reports by Okwor et al [19] which favoured the intraocular route to the oral route mostly citing possible destruction of vaccine antigens by gastrointestinal secretions as probable reasons for reduced optimization of uptake and subsequent immune response. Hence, phytogenic gum used in this study might have mitigated the destruction of vaccine antigens thereby optimizing uptake, response and subsequent reduced clinicopathologic feature following challenge by field virus.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This might account for the preferential protection offered by the oral route compared to the ocular one. This report is however at variance with reports by Okwor et al [19] which favoured the intraocular route to the oral route mostly citing possible destruction of vaccine antigens by gastrointestinal secretions as probable reasons for reduced optimization of uptake and subsequent immune response. Hence, phytogenic gum used in this study might have mitigated the destruction of vaccine antigens thereby optimizing uptake, response and subsequent reduced clinicopathologic feature following challenge by field virus.…”
Section: Discussioncontrasting
confidence: 97%
“…This validates the effectiveness of the vaccine used as well as the protection offered by both routes against mortality induced by Newcastle disease in birds. Protective capacities of vaccination through oral and ocular routes in chickens have already been reported in literature [19] . This is owing to the large surface area of the mucosa surface exposed to constant irritation and adapted for antigenic sampling and effector mechanisms [14] , [20] .…”
Section: Discussionmentioning
confidence: 86%
“…The minimum positive level serum is > 400 in ELISA antibody titre for IB living vaccine according to Kit of manufacturer. All vaccinated groups showed lymphocyte proliferation rates higher than control groups which can be explained by the fact that spraying and intranasal routes affect directly on the Harderian and paranasal glands that evolve a better immune responses (Okwor et al, 2013) Also, the effect on cell mediated response of T-cell expressed as Delta optical density (OD) was recorded for all groups . Lymphocyte proliferation rates were estimated by lymphocyte blastogenesis assay at 5 time points 3 rd , 5 th , 7 th , 14 th and 21 st days post vaccination as shown in Table (3).…”
Section: Resultsmentioning
confidence: 93%
“…The most common vaccination routes practiced in the industry are via intranasal aerosol spray (IN), DW, and intraocular or ED because these vaccination routes mimic a natural infection of ND [ 1 38 ]. Several studies have shown that the ED vaccination route produces the best highest antibody titer (8log 2 –9log 2 ), followed by intranasal spray (7log 2 ) and the DW and oral routes (3log 2 –6log 2 ) [ 38 39 40 ]. Furthermore, vaccination with EDs and spray offers better protection than DW for both genotype-matched and LaSota vaccines [ 24 26 38 39 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the ED vaccination route produces the best highest antibody titer (8log 2 –9log 2 ), followed by intranasal spray (7log 2 ) and the DW and oral routes (3log 2 –6log 2 ) [ 38 39 40 ]. Furthermore, vaccination with EDs and spray offers better protection than DW for both genotype-matched and LaSota vaccines [ 24 26 38 39 40 ]. Hence, these results and other studies indicate that the vaccination route is a critical determinant of vaccine-induced immunity.…”
Section: Discussionmentioning
confidence: 99%